2011
DOI: 10.3171/2011.7.focus11125
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle screw loosening in dynamic stabilization: incidence, risk, and outcome in 126 patients

Abstract: Object The long-term outcome of lumbar dynamic stabilization is uncertain. This study aimed to investigate the incidence, risk factors, and outcomes associated with screw loosening in a dynamic stabilization system. Methods The authors conducted a retrospective review of medical records, radiological studies, and clinical evaluations obtained in consecutive patients who underwent 1- or 2-level lumbar dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
135
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(149 citation statements)
references
References 31 publications
(27 reference statements)
12
135
1
1
Order By: Relevance
“…Previous single-treatment-arm studies of the Dynesys system also found radiographic evidence of screw loosening in 1.2%-19.8% of patients and 2.8%-4.7% of screws, and clinical deterioration resulting from the loosening of screws and necessitating revision surgery occurred in 0%-1.2% of patients. 16,17,26,30,31,34 Therefore, the risk of screw loosening and revision surgery after PDS using Dynesys seems to be considerably low.…”
Section: Evaluation Of Possible Disadvantages Of the Dynesys Systemmentioning
confidence: 99%
“…Previous single-treatment-arm studies of the Dynesys system also found radiographic evidence of screw loosening in 1.2%-19.8% of patients and 2.8%-4.7% of screws, and clinical deterioration resulting from the loosening of screws and necessitating revision surgery occurred in 0%-1.2% of patients. 16,17,26,30,31,34 Therefore, the risk of screw loosening and revision surgery after PDS using Dynesys seems to be considerably low.…”
Section: Evaluation Of Possible Disadvantages Of the Dynesys Systemmentioning
confidence: 99%
“…Pedicle screws require initial rigid fixation and longevity to stabilise the spine while the fusion mass forms. This procedure is broadly successful with low rates of screw loosening for standard screws (1-3) and increased rates for dynamic systems (4)(5)(6)(7). Screw loosening is a concern, with radiolucency around screws detrimental to fixation (8) and often warranting revision surgery (9).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the presence of nonspecific postoperative changes and metal-related imaging artefacts, interpretation of CT images is often not straightforward and is inconclusive. Thus, whether surgical reintervention is indicated based on conventional imaging may prove difficult to ascertain [5,6].…”
Section: Introductionmentioning
confidence: 99%